1995
DOI: 10.1111/j.1471-0528.1995.tb09136.x
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional ultrasound: abnormalities of the fetal face in surface and volume rendering mode

Abstract: Objective To evaluate three dimensional ultrasound in surface and volume rendering mode in fetal malformations of the face. Setting Day assessment unit in a university hospital. Subjects Four cases have been examined: two cases represented cleft lip, one case was a male with trisomy 13 (Patau syndrome) with proboscis, and one case represented a male fetus with unilateral anophthalmia. Conclusion A new technique of three dimensional ultrasound visualisation in fetal malformation using surface and volume renderi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 12 publications
1
35
0
1
Order By: Relevance
“…While some research groups are convinced that 3D imaging is able to convey additional image information [6,8,21], other authors merely report comparable results [13] and similar limitations as with conventional 2D ultrasound [22]. The psychological aspect that parents can better understand the given malformation if they see it on the 3D image is considered beneficial [23].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While some research groups are convinced that 3D imaging is able to convey additional image information [6,8,21], other authors merely report comparable results [13] and similar limitations as with conventional 2D ultrasound [22]. The psychological aspect that parents can better understand the given malformation if they see it on the 3D image is considered beneficial [23].…”
Section: Discussionmentioning
confidence: 97%
“…Recent scientific publications have shown that current technological advances lead to a broader area of application for the 3D imaging technique in connection with fetal organ analyses; the publications describe the routine depiction of fetal hands [4,5], cephalic [6][7][8][9][10] and vertebral structures [1,[11][12][13], cardiac volume [14], fetal ears [15], liver [16], lung [17], kidneys [18] and amniotic fluid [19]. The advantages and disadvantages of 3D image information compared to 2D imaging show considerable variations and are often a matter for controversial discussion between the different research groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cleft lips, micrognathia, malformed ears, and frontal bossing have all been reported to be better displayed by 3DUS. [16][17][18][19][20][21][22][23] To our knowledge, the use of 3DUS in a fetus with congenital epulis has not been reported. In addition to providing a surface-rendered display of the mass, which facilitated parental counseling, the 3DUS images showed a high likelihood of functional impairment of the nasal airway because the mass was seen obstructing both nares.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reviews of foetal applications of 3D ultrasound [121,156,173]. Much of this work has been concerned with the detection of foetal abnormalities [10], for instance cleft lip or other malformations of the face [107]. The visualisation of the foetal spine and thorax has also been achieved; important in evaluating skeletal dysplasia, abnormalities leading to a small thorax and subsequent pulmonary hypoplasia, and neural tube defects [132].…”
Section: Why Volume Measurement and Surface Visualisation?mentioning
confidence: 99%
“…This is generally achieved by attaching the transducer to a stepper motor, for linear [92,104,117,169], rotational [51,91,136], fan [20,69] or intravascular linear [102] scanning. This kind of approach has also been used in integrated transducers, for instance Kretz Technik's 4 Combison 330 [1,2] and 530 [30,107,121,173], which scans an entire pyramidal volume. Diagnostic Ultrasound Corporation also produce an integrated scanner and volume calculation device, Bladderscan 5 , specifically for urological use [118].…”
Section: Automatic Mechanical Localisationmentioning
confidence: 99%